Quantum-Resistant Cryptography in Cyber Security - Bhargavgowda, A.B.; Chitra, K. (INTI International University, 2025)
The emergence of quantum computing presents both significant opportunities and critical challenges for modern cybersecurity. While quantum systems promise advances in science, engineering, and artificial intelligence, they also pose a substantial threat to classical cryptographic techniques such as RSA, ECC, and other widely deployed public-key mechanisms. Quantum algorithms including Shor’s and Grover’s are expected to compromise these systems, placing sensitive data, financial infrastructures, and national security at risk. This paper examines the growing field of quantum-resistant, or post-quantum, cryptography with a focus on identifying constructions capable of withstanding quantum attacks. It provides a systematic overview of major post-quantum cryptographic families, including lattice-based, hash-based, code-based, multivariate, and isogeny-related schemes, and evaluates their current security assumptions, practical efficiency, and readiness for real-world deployment. Beyond technical considerations, the paper highlights the organizational and workforce implications of transitioning to quantum-safe systems, emphasizing the need for coordinated global standards and sustained cybersecurity training. This study underscores that building a quantum-secure digital future requires not only adopting resilient algorithms but also strengthening collaborative, adaptive, and proactive security practices.